Ricardo Palma and the Carlist suitor during his visit to Lima in 1887 - Mera Ávalos, Arnaldo (2023)
The present article on an unpublished subject in the historiography palmista seeks to expose the work of our distinguished traditionalist during the visit to our capital made by Don Carlos de Borbon, Carlist pretender to the crown of his elders with the numeral VII. To do so, we will previously expose the knowledge of this dynastic claim in the press of Lima, to then approach the visit itself and the performance that interests us. Keywords: History of Carlism, History of Spain, Ricardo Palma, History of Lima.